Effect of some biopolymers on the rheological behavior of surimi gel - Sarker, Md. Zaidul Islam; Saeed, Mohamed Abd Elgadir Mohamed; Ferdosh, Sahena; Akanda, Md. Jahurul Haque; Abd Manap, Mohd Yazid; Noda, Takahiro (MDPI, 2012)
The objective of this study was to investigate the effect of selected biopolymers on the rheological properties of surimi. In our paper, we highlight the functional properties and rheological aspects of some starch mixtures used in surimi. However, the influence of some other ingredients, such as cryoprotectants, mannans, and hydroxylpropylmethylcellulose (HPMC), on the rheological properties of surimi is also described. The outcome reveals that storage modulus increased with the addition of higher levels of starch. Moreover, the increasing starch level increased the breaking force, deformation, and gel strength of surimi as a result of the absorption of water by starch granules in the mixture to make the surimi more rigid. On the other hand, the addition of cryoprotectants, mannans, and HPMC improved the rheological properties of surimi. The data obtained in this paper could be beneficial particularly to the scientists who deal with food processing field.